The Cambridge companion to Victorian women's writing - Peterson, Linda H. (Cambridge, United Kingdom ; New York : Cambridge University Press, 2015)
"The Cambridge Companion to Victorian Women's Writing brings together chapters by leading scholars to provide innovative and comprehensive coverage of Victorian women writers' careers and literary achievements. While incorporating the scholarly insights of modern feminist criticism, it also reflects new approaches to women authors that have emerged with the rise of book history; periodical studies; performance studies; post-colonial studies; and scholarship on authorship, readership, and publishing. It traces the Victorian woman writer's career-from making her debut to working with publishers and editors to achieving literary fame-and challenges previous thinking about genres in which women contributed with success. Chapters on poetry, including a discussion of poetry in colonial and imperial contexts, reveal women's engagements with each other and male writers. Discussions on drama, life-writing, reviewing, history, travel writing, and children's literature uncover the remarkable achievement of women in fields relatively unknown"--
Introduction: Victorian women writers and modern literary criticism / Linda H. Peterson -- Part I. Victorian Women Writers' Careers: 1. Making a debut / Alexis Easley; 2. Becoming a professional writer / Joanne Shattock; 3. Working with publishers / Linda H. Peterson; 4. Assuming the role of editor / Beth Palmer; 5. Achieving fame and canonicity / Alison Chapman -- Part II. Victorian Women Writers' Achievements: Genres and Modes: 6. Poetry /Linda K. Hughes; 7. Silver-fork, industrial, and Gothic fiction / Ella Dzelzainis; 8. The Realist novel / Deirdre d'Albertis; 9. Sensation and New Woman fiction / Lyn Pykett; 10. Drama and theater / Katherine Newey; 11. Life writing / Carol Hanberry Mackay; 12. Travel writing / Tamara S. Wagner; 13. Colonial and imperial writing / Mary Ellis Gibson and Jason R. Rudy; 14. History writing / Deborah A. Logan; 15. Periodical writing / Margaret Beetham; 16. Reviewing / Joanne Wilkes; 17. Children's writing / Claudia Nelson.
Includes bibliographical references and index.
Keywords: English literature -- Women authors -- History and criticism; Women and literature -- Great Britain -- History -- 19th century; English literature -- 19th century -- History and criticism; Publishers and publishing -- Great Britain -- History -- 19th century